2013
DOI: 10.1002/jgrd.50132
|View full text |Cite
|
Sign up to set email alerts
|

Iodine chemistry in the eastern Pacific marine boundary layer

Abstract: [1] Observations of gas-phase iodine species were made during a field campaign in the eastern Pacific marine boundary layer (MBL). The Climate and Halogen Reactivity Tropical Experiment (CHARLEX) in the Galápagos Islands, running from September 2010 to present, is the first long-term ground-based study of trace gases in this region. Observations of gas-phase iodine species were made using long-path differential optical absorption spectroscopy (LP-DOAS), multi-axis DOAS (MAX-DOAS), and resonance and off-resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
79
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 79 publications
15
79
1
Order By: Relevance
“…Sources of tropospheric bromine in the model include emissions of CHBr 3 , CH 2 Br 2 and CH 3 Br, and transport of reactive bromine from the stratosphere. Debromination of sea-salt aerosol is not included in the model following the work of Schmidt et al (2016), which showed better agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free troposphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). Emission rates and bromine chemistry included in the model are described in detail by Parella et al (2012), with the bromine chemistry scheme described by 19 bimolecular reactions, 2 threebody reactions and 2 heterogeneous reactions using rate coefficients, heterogeneous reaction coefficients and photolysis cross sections recommended by Sander et al (2011).…”
Section: Global Modelsupporting
confidence: 56%
See 2 more Smart Citations
“…Sources of tropospheric bromine in the model include emissions of CHBr 3 , CH 2 Br 2 and CH 3 Br, and transport of reactive bromine from the stratosphere. Debromination of sea-salt aerosol is not included in the model following the work of Schmidt et al (2016), which showed better agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free troposphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). Emission rates and bromine chemistry included in the model are described in detail by Parella et al (2012), with the bromine chemistry scheme described by 19 bimolecular reactions, 2 threebody reactions and 2 heterogeneous reactions using rate coefficients, heterogeneous reaction coefficients and photolysis cross sections recommended by Sander et al (2011).…”
Section: Global Modelsupporting
confidence: 56%
“…The global model simulations reported here predict average mixing ratios of ∼ 0.5 ppt for BrO and ∼ 1 ppt for IO during SOS and thus underpredict BrO but perform well for IO. The underprediction of BrO at the Cape Verde Atmospheric Observatory results from recent model updates which exclude emissions of bromine species from sea-salt debromination (Schmidt et al, 2016) in order to provide improved agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free tro- posphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). If sea-salt debromination were included, daytime mixing ratios of BrO at the Cape Verde Atmospheric Observatory would be approximately 2 ppt, as shown by Parella et al (2012) and Schmidt et al (2016), and thus in closer agreement to the observations.…”
Section: Global Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Br and Cl radical concentrations are taken from a new GEOS-Chem simulation of tropospheric oxidant-aerosol chemistry by Schmidt et al (2016). Unlike Parrella et al (2012), this simulation does not include a bromine radical source from sea salt debromination as recent evidence suggests that BrO concentrations in the marine boundary layer (MBL) are generally sub-ppt (Gómez Martín et al, 2013;Wang et al, 2015). Simulated concentrations of Br in the free troposphere are, on the other hand, a factor of 2 higher than Parrella et al (2012), reflecting more extensive heterogeneous chemistry.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
“…The potential for tropospheric ozone destruction by iodine was recognized many decades ago (Chameides and Davis 1980) and confirmed later by measurements of the iodine oxide radical (IO) Read et al 2008;Mahajan et al 2010a, b;Gómez Martín et al 2013;Großmann et al 2013;Dix et al 2013;PradosRoman et al 2015). A ubiquitous global marine boundary layer (MBL) background of around 0.5-1 pptv IO has been established by these measurements.…”
Section: Introductionmentioning
confidence: 91%